2007
DOI: 10.1002/ijc.22413
|View full text |Cite
|
Sign up to set email alerts
|

CENP‐F expression is associated with poor prognosis and chromosomal instability in patients with primary breast cancer

Abstract: DNA microarrays have the potential to classify tumors according to their transcriptome. Tissue microarrays (TMAs) facilitate the validation of biomarkers by offering a high‐throughput approach to sample analysis. We reanalyzed a high profile breast cancer DNA microarray dataset containing 96 tumor samples using a powerful statistical approach, between group analyses. Among the genes we identified was centromere protein‐F (CENP‐F), a gene associated with poor prognosis. In a published follow‐up breast cancer DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 56 publications
9
102
0
Order By: Relevance
“…DNA microarrays and TMAs have also revealed that the upregulation of CENPF is significantly associated with a high tumor grade, a worse overall survival and a reduced metastasis-free survival in patients with primary breast cancer (17,25). Our present data indicated that the upregulation of CENPF mRNA expression was associated with a higher GS, an advanced pathological stage, the presence of metastasis, a shorter overall survival and PSA failure.…”
Section: Irs Of Cenpf In Our Cohortsupporting
confidence: 66%
See 1 more Smart Citation
“…DNA microarrays and TMAs have also revealed that the upregulation of CENPF is significantly associated with a high tumor grade, a worse overall survival and a reduced metastasis-free survival in patients with primary breast cancer (17,25). Our present data indicated that the upregulation of CENPF mRNA expression was associated with a higher GS, an advanced pathological stage, the presence of metastasis, a shorter overall survival and PSA failure.…”
Section: Irs Of Cenpf In Our Cohortsupporting
confidence: 66%
“…It has been demonstrated that CENPF is upregulated in primary breast cancer (25). As for hepatocellular carcinoma (HCC), CENPF has been found to be overexpressed in tumor tissue compared with non-tumor tissue (26).…”
Section: Irs Of Cenpf In Our Cohortmentioning
confidence: 99%
“…Elevated Cenp-F expression has been associated with poor prognosis in patients with breast cancer, leading to the suggestion that Cenp-F overexpression might contribute to tumorigenesis (O'Brien et al, 2007). Surprisingly, we observed no obvious mitotic or cell-cycle defects following overexpression of various non-degradable Cenp-F mutants (data not shown) and as such the role of Cenp-F degradation remains unclear.…”
Section: The Role Of Cenp-f Degradationmentioning
confidence: 67%
“…This molecule has also been described as a biomarker associated with poor outcome in breast cancer (52). MMP9, a component of the extracellular matrix, has been shown to be upregulated in atypical and anaplastic meningiomas (18,53) and has been proposed as a potential target for therapy in meningiomas (54).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%